Foot lesions - Swinyer, Leonard J., 1940-; Marion & Roberta Sulzberger Institute for Dermatologic Communication and Education; American Academy of Dermatology. Committee on Audiovisual Education ([Evanston, Ill.] : American Academy of Dermatology, Committee on Audiovisual Education, 1987)
(Producer) A collection of prevalent dermatoses of the foot due to papulosquamous, heritable, and vascular disorders; injury; inflammation of vessels; hypersensitivity; infection; and tumors
'From the collection of Leonard J. Swinyer.'
Keywords: Foot dermatoses